Receptor for Advanced Glycation Endproducts (RAGE), Its Ligands, and Soluble RAGE: Potential Biomarkers for Diagnosis and Therapeutic Targets for Human Renal Diseases - Eun Ji Lee; Jong Hoon Park (Genomics & Informatics)
Receptor for advanced glycation endproducts (RAGE) is a multi-ligand receptor that is able to bind several different ligands, including advanced glycation endproducts, high-mobility group protein (B)1 (HMGB1), S-100 calcium-binding protein, amyloid-β-protein, Mac-1, and phosphatidylserine. Its interaction is engaged in critical cellular processes, such as inflammation, proliferation, apoptosis, autophagy, and migration, and dysregulation of RAGE and its ligands leads to the development of numerous human diseases. In this review, we summarize the signaling pathways regulated by RAGE and its ligands identified up to date and demonstrate the effects of hyper-activation of RAGE signals on human diseases, focused mainly on renal disorders. Finally, we propose that RAGE and its ligands are the potential targets for the diagnosis, monitoring, and treatment of numerous renal diseases.